Post-processing Methods to Improve Strength of Particle-Bed 3D Printed Geopolymer for Digital Construction Applications - Nematollahi, Behzad; Xia, Ming; Sanjayan, Jay (Frontiers in Materials, 2019)
The strength of powder-based 3D printed geopolymer samples immediately after the de-powdering process (‘green’ strength) is inherently very low. Therefore, different post-processing techniques have been explored in the previous study of the authors to enhance the ‘green’ strength of the printed geopolymer. The highest strength of around 30 MPa was achieved for the printed geopolymer sample cured in an alkaline solution for 7 days at 60°C. Although this strength is sufficient for a wide range of construction applications, the necessity for the heat curing procedure, which requires significant amount of energy, can compromise the sustainability credentials of the developed powder-based 3D printed geopolymer and limit its commercial viability and large-scale applications in the construction industry. To tackle this issue, this study aims to develop a new post-processing method which eliminates the necessity for the heat curing. The influences of type of curing medium, duration and temperature of curing, and testing direction on the compressive strength of the printed geopolymer were investigated. The ‘green’ printed geopolymer samples were immersed in four different curing mediums, including two sodium (Na)-based and two potassium (K)-based activators with different alakli modulus (SiO2/M2O where M=Na or K), and cured at two different curing temperatures (ambient temperature (23°C) versus 60°C) for 7 and 28 days. The compressive strength of the ‘post-processed’ printed geopolymer specimens was measured in two different testing directions, namely the binder jetting direction and layer stacking direction. The results showed that the 28-day compressive strength of the ambient temperature cured printed geopolymer sample was comparable to the 7-day compressive strength of the corresponding heat cured sample. Therefore, the feasibility of enhancing the strength of printed geopolymer by curing in an alkaline solution at ambient temperature was established. This newly developed post-processing method based on the ambient temperature curing is more viable and less energy-intensive, yet provides comparable strength, as compared to the previously developed post-processing method based on the heat curing. The results also showed that the strength of the printed geopolymer samples cured in the K-based activators was lower than that of the specimens cured in the Na-based activators.